Larvicidal efficacy of crude and fractionated extracts of Dracaena loureiri Gagnep against Aedes aegypti, Aedes albopictus, Culex quinquefasciatus, and Anopheles minimus mosquito vectors - Damrongpan Thongwat; Ratchanaporn Chokchaisiri; Lucksagoon Ganranoo; Nophawan Bunchu (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To evaluate the larvicidal efficacy of crude and fractionated extracts of Dracaena loureiri endocarp against Aedes aegypti, Aedes albopictus, Culex quinquefasciatus, and Anopheles minimus mosquitos. Methods: Larvicidal activity was tested according to World Health Organization standard protocol. The third-stage larvae of each mosquito species were exposed to various concentrations of Dracaena loureiri crude extract and six groups of Dracaena loureiri fractionated extracts (RC-DT 009–014). Larval mortality rates were observed after 24 h and 48 h of exposure. Then, a computerized probit analysis of the mortality data was performed to determine lethal concentration 50 (LC50) and lethal concentration 90 values. Results: Anopheles minimus larvae (24-h LC50 77.88 mg/L) had the highest susceptibility to crude extract, whereas others (Aedes aegypti, 24-h LC50 224.73 mg/L; Aedes albopictus, 24-h LC50 261.75 mg/L; and Culex quinquefasciatus, 24-h LC50 282.86 mg/L) were significantly less susceptible. The most effective groups of fractionated extracts were RC-DT 012 and RC-DT 013. The mosquito species most susceptible to fractionated extracts was Culex quinquefasciatus, with 24-h LC50 values of 0.66 and 0.94 mg/L for RC-DT 012 and RC-DT 013, respectively. Conclusions: The larvicidal activity of fractionated extracts is more effective than that of crude extract against all tested mosquito species. For the most effective alternative larvicide, purification and a phytochemical constituent analysis must be performed.